Effective Management and Motivation of Employees During Overtime Work (Journal of Universal Excellence, 2026)
Research Question (RQ): What should an effective manager be like to achieve the organization's goals together with employees? What types of rewards do managers use to successfully motivate employees during overtime work? How do managers cope with the burden of overtime on employees?Purpose: The purpose of this article is to investigate how managers achieve organizational goals, what types of rewards they use for motivation during overtime work, and how they deal with the workload of employees during overtime work.Method:  The research was conducted using a qualitative method. Using the qualitative method, we conducted ten semi-structured interviews with managers in various industries with the aim of studying the attitudes of managers, what an effective manager is for them, what types of rewards they use when working overtime, and how they deal with increased workload, such as overtime work. overloading of employees. We processed the qualitative data using the online program Atlas.ti and compared the findings with theoretical findings.Results:  The results of the qualitative research showed that an effective manager must have well-developed communication skills, must know how to set clear goals, motivate employees and gain the trust of employees so that he can achieve the set goals together with the employees. The managers interviewed pointed out that financial rewards are most often used to motivate overtime work. Managers also use praise and recognition, offer opportunities for advancement and allow employees a day off. In order to avoid overloading employees during overtime work, managers ensure well-organized work, provide support and understanding to employees, ensure rest and relaxation, appropriately distribute working time among employees, adjust the schedule and try to manage stress in the work environment they lead as efficiently as possible.Organization: Effective leadership and motivation of employees in organizations are key factors for ensuring success in the organization. Overtime work is important in the organization of work and the coordination of work processes in a production organization. If the organization were to take into account the results obtained by the managers, this would be a gain for the organization as it would ensure greater productivity and efficiency of the employees.Society: Effective management and motivation of employees to work overtime can help increase the productivity and competitiveness of organizations, which in turn can lead to economic growth.Originality: The originality of the research lies in the fact that it focuses on investigating the effective management and motivation of overtime employees in various industries in the Southeast region.Limitations/Future Research: The sample was limited to managers in various industries in the Southeast region, so caution should be exercised when extrapolating conclusions about effective leadership and overtime employee motivation to other regions or industries. The research focuses on overtime work and its consequences for employees, but does not take into account other factors, such as organizational culture, structure or company policies, which may influence effective management and employee motivation.
Keywords: effective management; overtime work; motivation; communication; overload